Akuntabilitas, Transparansi, Kualitas Pelayanan dan Niat Muzakki Membayar Zakat - Waliyulloh, Faruq; Hasibuan, Henny Triyana (E-Jurnal Akuntansi, 2023)
The research objective is to identify the influence of muzakki's intention to pay zakat, these influences include accountability, transparency, and quality of service. The research was conducted at the National Amil Zakat Agency in Denpasar City, the number of respondents was 116 participants, selected through non-probability sampling method and using saturated sampling technique. The type of data used is primary data by collecting it by distributing questionnaires to the respondents, then the data is analyzed through multiple linear regression analysis. Based on the results of the analysis, it proves that accountability and transparency affect muzakki's intention to pay zakat, while service quality does not affect muzakki's intention to pay zakat. Keywords: Accountability; Transparency; Quality of Service; Muzakki's Intention